Mechanical properties of hemp fiber composites with carbon nanotubes reinforcement - H. Longkullabutra (2018)
An experimental was investigated the condition of reinforcement of hemp fiber and hemp fiber/epoxy resin composites with carbon nanotubes (CNTs).The CNTs were mixed with several liquid such as ethanol, latex, water glue and epoxy resin. These mixtures were added to hemp fiber and prepared the hemp fiber/epoxy resin composites. The mechanical properties of both fiber and composite samples were measured. It was found that the mixture of epoxy resin and CNTs with CNTs ratio of 20 vol% in hemp fiber showed the highest tensile strength of 25.43 N. and the same mixture in hemp fiber/epoxy resin composites showed the highest tensile strength of 31.82 MPa and elongation of 7.40 %. © 2008 Trans Tech Publications, Switzerland.